"Maximum Autonomy with Divided Sovereignty": An Extrapolation of Eqbal Ahmad's Solution to the Kashmir Conflict. (2nd October 2022) - Varigonda, Kesava Chandra
Abstract : The Kashmir conflict, ongoing for over seventy years, is no closer to a resolution. The separatist insurgency that had emerged in the late 1980s, along with attendant military action, has claimed over 50, 000 lives till date. However, the three major parties to the conflict, the Indian state, the Pakistani state and the Kashmiri separatist movement continue to have mutually-intractable positions. How might these positions be reconciled? Eqbal Ahmad's proposal attempts to reconcile the three positions through the prism of "maximum autonomy with divided sovereignty." This essay extrapolates Ahmad's proposal, and presents two distinct facets to the solution: Azad Jammu and Kashmir and Gilgit-Baltistin to become full territories within the Pakistani state; the Jammu region and Ladakh to become full territories within the Indian state; and the Kashmir valley to become an independent Kashmir state. The independent Kashmir state would share its sovereignty, to a limited extent, with India and Pakistan. This paper extrapolates the contours of Ahmad's proposal, particularly in the context of previous attempts by India, Pakistan and Kashmiri separatists to force a resolution in their favor.